Transcatheter pulmonary valve implant in a patient with a previous pulmonary valve-in-valve. Issue 1 (July 2022) - Kim, Wan Cheol; Taliotis, Demetris; Turner, Mark
Abstract: Increasing numbers of patients with congenital heart disease now survive well into adulthood. Often, these patients already had surgery to correct their congenital lesions from early life. Patients with tetralogy of Fallot commonly require several pulmonary valve replacements in their lifetime. This report highlights the utility of percutaneous pulmonary valve implant inside the two prior prosthetic valves avoiding a third sternotomy, in a young adult patient who developed severe prosthetic pulmonary valve stenosis. Learning objective: To understand the potential therapeutic option of transcatheter pulmonary valve implant inside a dilatable stented surgical bioprosthesis with an existing valve-in-valve in situ as part of lifetime management.